The Commutation Matrices of Elements in Kronecker Quaternion Groups - Yanita Yanita; Eka Purwanti; Lyra Yulianti (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
This article discusses the commutation matrix in the Kronecker quaternion group; that is, a non-abelian group whose 32 elements are matrices of 4 × 4 size, with entries in the set of complex numbers. The purpose of this paper is to describe the commutation matrices obtained in relation to the matrices in this group. The commutation matrix is a permutation matrix that associates the relationship between the vec and vec of the transpose matrix. Based on the classification of matrices in the Kronecker quaternion group, there are 16 classification of commutation matrices for the matrices in this group.